Physiological shear stress suppresses apoptosis in human pulmonary microvascular endothelial cells - Simin Yan; Nicolas M. Philip; Samuel T. Murray; Xin Yun; Michael P. Croglio; Karthik Suresh; Mahendra Damarla; Larissa A. Shimoda; Todd M. Kolb (Physiological Reports)
Abstract Physiological shear stress contributes to maintaining endothelial cell homeostasis, including suppression of apoptosis. In the pulmonary circulation, diseases such as pulmonary embolism and pulmonary hypertension result in alterations in shear stress. Shear stress has been reported to suppress endothelial apoptosis through phosphatidylinositol 3‐kinase (PI3K) activation, but evidence from human pulmonary microvascular endothelial cells (PMVECs) is lacking. We hypothesized that physiological shear stress activates PI3K to reduce apoptosis in human PMVECs. We utilized the orbital shaker model of shear stress to test our hypothesis. Apoptosis was evaluated by measuring chromatin condensation, caspase 3/7 activity, and DNA fragmentation. We found that shear stress caused a rapid and sustained increase in protein kinase B (Akt) phosphorylation, a surrogate for activated PI3K, in human PMVECs. Under static conditions, PI3K inhibition with LY294002 or challenge with the kinase inhibitor staurosporine (STS) induced apoptosis in PMVECs. Following exposure to shear stress for 24 h, LY294002‐ and STS‐induced apoptosis was reduced. The anti‐apoptotic effect of shear stress in STS‐challenged cells was reversed by PI3K inhibition. We conclude that physiological shear stress increases PI3K/Akt activity and suppresses apoptosis in normal human PMVECs.